Lattice Boltzmann application on the PCM solidification within a rectangular finned container. (25th May 2015) - Talati, F.; Taghilou, M.
Abstract: This work presents an application of lattice Boltzmann method (LBM) for solidification of phase change material (PCM) within a rectangular finned container. To do this, an implicit lattice Boltzmann method is applied into two rectangular containers. At first the problem of PCM solidification within a rectangular fined container with constant wall temperatures is solved and compared with available approximate analytical results. The LBM results are compared with results of finite volume method (FVM), and then it was used to analyze accuracy condition for presenting the analytical solutions. Second, the LBM is used to obtain the temperature distribution through the composite plane wall containing rectangular PCM container with convective boundary conditions. The effect of PCM within the composite plane wall is studied as a heat source during freezing. It is shown that locating the PCM container inside the wall could efficiently prevent the heat losses, when it is exposed to the cold air flow, and the rate of solidification is extremely controlled by containers material. Also, it is confirmed that the current LBM effectively saves the running time several times compared to finite volume method. Highlights: LBM is used to simulate the PCM solidification inside the rectangular container. The maximum required time for freezing the PCM occurs at the aspect ratio of 0.5. Analytical solution overestimates the required time for PCM solidification. Maximum analytical overestimation occurs at aspect ratio of 0.5. Heat loss decreases by locating the PCM inside the composite plane wall.